Peningkatan Pengetahuan Remaja tentang Prakonsepsi melalui Video - Setyawati, Irni; Dian Soekmawaty Riezqy Ariendha; Kusniyati Utami; Nurul Fatmawati; Hardaniyati (Jurnal Ilmiah Pengabdian dan Inovasi, 2025)
The aims of this community service to provide adolescents knowledge about preconception in the Dasan Kolo of Mataram City. The method used in this activity is health education through video viewing and leaflet. The results of this community service are the average knowledge score of adolescents about preconception before the video screening and leaflet distribution was 47.5, and the average knowledge score of adolescents about preconception after watching the video and receiving the leaflets was 76.3. There was an increase from the average identification score to the average evaluation score. The average increase in female adolescents' knowledge about preconception was 28.8. The implications of this community service are that adolescents' knowledge about preconceptions increases and adolescents are more interested in video material. Video educational media is expected to be used and developed as a further educational medium to improve adolescents' knowledge and skills.